2020
DOI: 10.1109/lawp.2020.3018589
|View full text |Cite
|
Sign up to set email alerts
|

A Wideband 3-D Printed Reflectarray Antenna With Mechanically Reconfigurable Polarization

Abstract: This letter describes a wideband and polarizationreconfigurable reflectarray (RA) antenna using 3D printed technology for 5G millimeter-wave applications. An air-perforated dielectric stub is proposed as a unit cell (UC) to provide simultaneous polarization-rotation and phase-shifting capabilities. By optimizing the dimensions of the UC, four UCs are found to offer a 90-degree out of phase for transverse electric (TE) and transverse magnetic (TM) incidence waves and a 2-bit reflection phase of {-π, -π/2, 0, π/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…This kind of reflectarrays provide very wideband response in frequency. Another version of a dielectric reflectarray is published in [157], where the protrusion (C-shaped in this case) is not supported on a dielectric panel but on the ground plane directly. The properties are actually similar to the dielectric reflectarrays previously cited.…”
Section: Designsmentioning
confidence: 99%
“…This kind of reflectarrays provide very wideband response in frequency. Another version of a dielectric reflectarray is published in [157], where the protrusion (C-shaped in this case) is not supported on a dielectric panel but on the ground plane directly. The properties are actually similar to the dielectric reflectarrays previously cited.…”
Section: Designsmentioning
confidence: 99%
“…Existing research have shown that dielectric reflectarray have low loss and well performance in microwave frequencies, which can achieve ultra-wideband. [20][21][22][23][24] The dielectric reflectarray of literature 20 adopts the fused deposition modeling (FDM) printed to achieve reconfigurable polarization mechanically. The dielectric resonator reflectarray 21 achieved a gain of 28 dBi at 30 GHz in FDM printed.…”
Section: Introductionmentioning
confidence: 99%
“…When the electromagnetic wave is perpendicular to the DRU, it is equivalent to a transmission line 20 to analyze its reflection phase θ width L.…”
Section: Introductionmentioning
confidence: 99%
“…With the fast prototyping capability of irregular shapes, three-dimensional (3D) printing has been used for fabricating DR reflectarrays in recent years [15]- [18]. [15] and [17] both proposed 3D printed dielectric reflectarrays with variable height elements at sub-millimeter-waves.…”
mentioning
confidence: 99%
“…By using the acrylonitrile butadiene styrene (ABS) material, a 3D-printed dielectric reflectarray with variable width unit cells was designed in [16]. In [18], a polarization-reconfigurable reflectarray was realized by 3D printing for 5G millimeterwave applications. All these designs are also limited to low relative permittivity materials (ɛr < 4.4) and therefore resulting in a large size or non-planar configuration.…”
mentioning
confidence: 99%